Synthesis of Imidazolidin-2-ones from trans-(R,R)-Diaminocyclohexane: A Statistical Analysis-Based Pseudo-Multicomponent Protocol - Catalina Hoyos-Orozco; Lili Dahiana Becerra; Diego Quiroga (Molecules)
A pseudo-multicomponent one-pot protocol for the synthesis of 1,3-disubstituted imidazolidin-2-one is described, employing trans-(R,R)-diaminocyclohexane for the in situ formation of the Schiff base, followed by reduction to produce the respective diamine and cyclization with carbonyldiimidazole (CDI). This approach utilizes statistical analysis to optimize the reaction conditions, allowing a pseudo-multicomponent protocol to be proposed. The developed method demonstrates sustainability, efficiency, and potential applications in green chemistry, achieving yields ranging from 55% to 81%. This represents a significant advance in synthesizing heterocyclic compounds with biological and pharmacological applications.